Glycaemic Status of Diabetic Patients Attending a District Diabetic Hospital in Bangladesh - Ekram, ARM Saifuddin; Huda, M Nazmul (TAJ: Journal of Teachers Association, 2009)
doi: 10.3329/taj.v21i2.3786 TAJ 2008; 21(2)